Endothelial and Epithelial Cell Transition to a Mesenchymal Phenotype Was Delineated by Nestin Expression. Issue 7 (2nd December 2015) - Chabot, Andréanne; Hertig, Vanessa; Boscher, Elena; Nguyen, Quang Trinh; Boivin, Benoît; Chebli, Jasmine; Bissonnette, lyse; Villeneuve, Louis; Brochiero, Emmanuelle; Dupuis, jocelyn; Calderone, Angelino
Abstract : Endothelial and epithelial cell transition to a mesenchymal phenotype was identified as cellular paradigms implicated in the appearance of fibroblasts and development of reactive fibrosis in interstitial lung disease. The intermediate filament protein nestin was highly expressed in fibrotic tissue, detected in fibroblasts and participated in proliferation and migration. The present study tested the hypothesis that the transition of endothelial and epithelial cells to a mesenchymal phenotype was delineated by nestin expression. Three weeks following hypobaric hypoxia, adult male Sprague‐Dawley rats characterized by alveolar and perivascular lung fibrosis were associated with increased nestin protein and mRNA levels and marked appearance of nestin/collagen type I (+) ‐fibroblasts. In the perivascular region of hypobaric hypoxic rats, displaced CD31 (+) ‐endothelial cells were detected, exhibited a mesenchymal phenotype and co‐expressed nestin. Likewise, epithelial cells in the lungs of hypobaric hypoxic rats transitioned to a mesenchymal phenotype distinguished by the co‐expression of E‐cadherin and collagen. Following the removal of FBS from primary passage rat alveolar epithelial cells, TGF‐β1 was detected in the media and a subpopulation acquired a mesenchymal phenotype characterized by E‐cadherin downregulation and concomitant induction of collagen and nestin. Bone morphogenic protein‐7 treatment of alveolar epithelial cells prevented E‐cadherin downregulation, suppressed collagen induction but partially inhibited nestin expression. These data support the premise that the transition of endothelial and epithelial cells to a mesenchymal cell may have contributed in part to the appearance nestin/collagen type I (+) ‐fibroblasts and the reactive fibrotic response in the lungs of hypobaric hypoxic rats. J. Cell. Physiol. 231: 1601–1610, 2016. © 2015 Wiley Periodicals, Inc.